PTU-011 Impact of weight loss after bariatric surgery on adenoma detection rate in colonoscopy: a case control study. (22nd June 2015) - Cracco, A; Tandon, K; Rodrigues, FG; Imam, M; Rosenthal, RJ; Castro, F; Dasilva, G; Wexner, SD
Abstract : Introduction: Studies have determined that a high Body Mass Index (BMI) is associated with an increased risk of colonic adenoma. There is a paucity of data on the impact of weight loss in morbidly obese populations and its effects on colonic adenoma detection rate (ADR). This study aimed to determine the impact of weight loss after bariatric surgery on the adenoma detection rate on colonoscopy. Method: After IRB approval a retrospective review of prospectively collected data was performed for patients who underwent bariatric surgery between 2004–2012. Patients who had a colonoscopy after bariatric surgery were identified as cases. Controls included a random sample of patients who had a colonoscopy during the same timeperiod. They were matched by age and gender in 1:4 ratio of case to controls. Patients with poor bowel preparation or Ottawa score >11 were excluded. Patient demographics, baseline BMI and BMI at colonoscopy, weight change, co-morbidities, type of bariatric surgery and presence/absence of adenoma or advanced adenoma (AA) were collected. Adenoma and AA detection rates were analysed by age (<40; 40–49; 50–59; >60 years) and compared between the two groups. AA was defined as tubular adenoma or serrated polyp ≥10 mm in diameter, villous features, high-grade dysplasia. Hyperplastic polyps ≥10 mm were classified as advanced adenoma. Results: 194 cases and 797 controls were included (females 68%). The mean age of patients was 51.5 years. 62.3% of the patients underwent gastric bypass, 28.5% sleeve gastrectomy and 9.2% gastric band. Average decrease in BMI after bariatric surgery was 13 ± 5.5 kg/m 2 . The median follow-up was 31.6 (2–107) months. The average BMI at the time of colonoscopy of the cases and controls was 32 ± 6 kg/m 2 and 27.4 ± 5.5 kg/m 2 respectively. There was no significant difference in adenoma and AA detection rate between groups analysed by age. Among those who underwent bariatric surgery, there was no relation between the occurrence of adenomas and BMI reduction; however the effect of BMI reduction on the occurrence of AA did approach significance. (P = 0.05). The time interval between bariatric surgery and colonoscopy was not related to the incidence of adenoma nor AA. Conclusion: Despite the differences in BMI between the patients and controls we found no difference in adenoma or advanced adenoma detection. BMI reduction after bariatric surgery did not affect the presence of adenomas but may be associated with a significant decrease in the risk of developing AA. Further studies with large population data might be required to validate these findings. Disclosure of interest: None Declared.